Frameshift Mutation Confers Function as Virulence Factor to Leucine-Rich Repeat Protein from Acidovorax avenae - Kondo, Machiko; Hirai, Hiroyuki; Furukawa, Takehito; Yoshida, Yuki; Suzuki, Aika; Kawaguchi, Takemasa; Che, Fang-Sik (Frontiers in Plant Science, 2017)
Many plant pathogens inject type III (T3SS) effectors into host cells to suppress host immunity and promote successful infection. The bacterial pathogen Acidovorax avenae causes brown stripe symptom in many species of monocotyledonous plants; however, individual strains of each pathogen infect only one host species. T3SS-deleted mutants of A. avenae K1 (virulent to rice) or N1141 (virulent to finger millet) caused no symptom in each host plant, suggesting that T3SS effectors are involved in the symptom formation. To identify T3SS effectors as virulence factors, we performed whole-genome and predictive analyses. Although the nucleotide sequence of the novel leucine-rich repeat protein (Lrp) gene of N1141 had high sequence identity with K1 Lrp, the amino acid sequences of the encoded proteins were quite different due to a 1-bp insertion within the K1 Lrp gene. An Lrp-deleted K1 strain (KΔLrp) did not cause brown stripe symptom in rice (host plant for K1); by contrast, the analogous mutation in N1141 (NΔLrp) did not interfere with infection of finger millet. In addition, NΔLrp retained the ability to induce effector-triggered immunity (ETI), including hypersensitive response cell death and expression of ETI-related genes. These data indicated that K1 Lrp functions as a virulence factor in rice, whereas N1141 Lrp does not play a similar role in finger millet. Yeast two-hybrid screening revealed that K1 Lrp interacts with oryzain α, a pathogenesis-related protein of the cysteine protease family, whereas N1141 Lrp, which contains LRR domains, does not. This specific interaction between K1 Lrp and oryzain α was confirmed by Bimolecular fluorescence complementation assay in rice cells. Thus, K1 Lrp protein may have acquired its function as virulence factor in rice due to a frameshift mutation.